How to adapt winemaking practices to modified grape composition under climate change conditions - Sylvie Dequin; Jean-Louis Escudier; Marina Bely; Jessica Noble; Warren Albertin; Isabelle Masneuf-Pomarède; Philippe Marullo; Jean-Michel Salmon; Jean Marie Sablayrolles (OENO One, 2017)
Aim: In the context of climate change, adaptation of enological practices and implementation of novel techniques are major challenges for winemakers. The potential interventions are linked in particular with the alcohol content and the global acidity of wine. Here, we review current microbiological and technological strategies to overcome such issues.